1971
DOI: 10.1152/ajplegacy.1971.220.3.773
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid glands and mitotic stimulation in rat bone marrow after hemorrhage

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

1971
1971
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 0 publications
0
18
0
3
Order By: Relevance
“…Four decades ago, Perris et al reported a coupling of the bone marrow response to acute blood loss with the release of PTH. 4 However, Singbrant et al showed no significant change of PTH in Epo-treatment. 1 Instead, they suggested the involvement of Oncostatin M (OsM), which is produced by erythroblasts.…”
Section: T He Glycoprotein Erythropoietin (Epo)mentioning
confidence: 97%
See 1 more Smart Citation
“…Four decades ago, Perris et al reported a coupling of the bone marrow response to acute blood loss with the release of PTH. 4 However, Singbrant et al showed no significant change of PTH in Epo-treatment. 1 Instead, they suggested the involvement of Oncostatin M (OsM), which is produced by erythroblasts.…”
Section: T He Glycoprotein Erythropoietin (Epo)mentioning
confidence: 97%
“…Low-density lipoprotein (LDL) deposited in the vessel wall can stimulate inflammation and oxidative stress, generating oxidized LDL (oxLDL). [2][3][4] OxLDL promotes pro-inflammatory responses in monocytes, starting a long process that leads to dysfunctional arteries, fatty streaks, and fibrous plaques.…”
Section: T He Glycoprotein Erythropoietin (Epo)mentioning
confidence: 99%
“…At the cellular level, PTH was shown to increase proliferation in the bone marrow and liver in vivo and in T-lymphocytes in vitro [46]. In contrast, the active form of vitamin-D, 1,25-dihydroxycholecalciferol, appears to suppress cell proliferation and to promote differentiation of immature or neoplastic cells [47].…”
Section: Parathyroid Hormone Excess and Deficiency Of 125-dihydroxycmentioning
confidence: 99%
“…These data indicate that PTH affects directly the erythroid precursors by a mechanism similar to that of erythropoietin. The inhibitory effect on the RNA synthesis observed with large doses of PTH may explain at least one of the causes of the anemia reported in patients with primary hyperparathyroidism.Parathyroid hormone (PTH) and cal cium were shown to stimulate lymphopoie sis and erythropoiesis [10][11][12]. Removal of the parathyroid gland caused a marked re duction of the mitotic activity in rat bonemarrow cells, which in turn was followed by a pronounced decrease in the size of mar row nucleated cells [14].…”
mentioning
confidence: 99%